Enhanced thermal conductivity and mechanical property through boron nitride hot string in polyvinylidene fluoride fibers by electrospinning. (1st March 2018) - Zhang, Dong-Li; Zha, Jun-Wei; Li, Wei-Kang; Li, Chao-Qun; Wang, Si-Jiao; Wen, Yongqiang; Dang, Zhi-Min
Abstract: The electrospun polyvinylidene fluoride (PVDF) based modified boron nitride (m-BN) composite with high thermal conductivity and flexible mechanical property was successfully fabricated by electrospinning method. The uniform dispersion and ordered orientation of m-BN in the m-BN/PVDF composites form a hot string, denoted as a series of thermal conduction fillers, in the direction of the fiber. Hence, the thermal conductivity of the m-BN/PVDF film could reach to 7.29 W m −1 K −1 with the addition of 30 wt% m-BN. Besides, the obtained composites also show improved mechanical properties with the tensile strength of 24.06 MPa, low dielectric permittivity of 2.45 and dielectric loss of 0.0242 @ 10 3 Hz. Therefore, this work provides a new route to prepare the high thermal conductivity films with potential application as flexible power devices.